Argument-Mapping menggunakan ChatGPT untuk Meningkatkan Kualitas Argumen Ilmiah bagi Mahasiswa - Nakrowi, Zain Syaifudin; Nugraha, Haris Santosa; Yanti, Nafri (Jurnal Sosioteknologi, 2025)
This study explores the impact of Argument Mapping (AM) assisted by ChatGPT on students' ability to write scientific arguments. While AM has been shown to enhance argumentative skills, there is limited research on integrating generative technologies like ChatGPT into the AM model for writing instruction. This study examines ChatGPT's role in helping students in the Nursing and Primary School Teacher Education (PGSD) programs develop clearer and more logical argument structures. A mixed-methods explanatory sequential design was used, incorporating quantitative pre- and post-tests to measure improvements in argumentative writing and qualitative semi-structured interviews to gather students' perceptions. Results show that AM supported by ChatGPT significantly enhances students' argumentative writing skills, particularly in clarity and argument structure in depth. The findings suggest that ChatGPT aids writing and fosters critical thinking. However, ethical considerations, including plagiarism awareness, are important when using this technology. This study contributes to the literature by highlighting AI's potential to improve argumentative writing skills and promoting the integration of technology in education for developing critical thinking.